Microstructural Analysis and Antibacterial Response of Zn2+/Mg2+ Dual Doped β-Tricalcium Phosphate Bioceramics - Ammar Zeidan Alshemary; Huda Basim Qasim; Ali Taha Saleh (Indonesian Journal of Chemistry, 2022)
This article evaluates the impact of the addition of zinc (Zn) and magnesium (Mg) on the structural, morphological, and antibacterial characteristics of β-tricalcium phosphates (hereafter called Zn/Mg-βTCP) prepared using the microwave (MW) assisted wet precipitation method in which the Ca deficient apatite [Ca9-(x+y)MgxZny(HPO4)(PO4)5 (OH)] was calcined for 2 h at 1000 °C. The prepared samples were characterized using XRD, FTIR, and FESEM measurements. The XRD patterns of the samples showed a steady decrease in the lattice parameters with an increase in Mg2+ and Zn2+ content. The FESEM images of the samples disclosed the morphological changes due to the Mg2+/Zn2+ co-doping. The inclusion of Mg2+ and Zn2+ into the βTCP was shown to induce excellent bioactivities that were absent in the pristine βTCP. Enhancement, coupled with good antimicrobial properties against Escherichia coli (E. coli), suggests that Mg2+/Zn2+ co-doping TCP can be developed further into antibacterial bone cement. As synthesized, it would be considered a potential biomaterial for orthopedic applications.